The double knockdown of the mitochondrial uncoupling protein isoforms reveals partial redundant roles during Arabidopsis thaliana vegetative and reproductive development - Lima, Rômulo Pedro Macêdo [UNESP]; Nunes-Laitz, Alessandra Vasconcellos; Arcuri, Mariana de Lara Campos [UNESP]; Campos, Felipe Girotto [UNESP]; Joca, Thaís Arruda Costa [UNESP]; Monteiro, Gean Charles [UNESP]; Kushima, Hélio [UNESP]; Lima, Giuseppina Pace Pereira [UNESP]; de Almeida, Luiz Fernando Rolim [UNESP]; Barreto, Pedro [UNESP]; de Godoy Maia, Ivan [UNESP] (My University, 2022)
Mitochondrial uncoupling proteins (UCPs) are specialized proteins capable of dissipating the proton electrochemical gradient generated in respiration independent of ATP synthesis. Three UCP coding genes with distinct expression patterns have been identified in Arabidopsis thaliana (namely UCP1, UCP2 and UCP3). Here, we generated T-DNA double-insertion mutants (ucp1 ucp2, ucp1 ucp3 and ucp2 ucp3) to investigate the functionality of the Arabidopsis UCP isoforms. A strong compensatory effect of the wild-type UCP gene was found in the double-knockdown lines. Higher levels of reactive oxygen species (ROS) were observed in vegetative and reproductive organs of double mutant plants. This exacerbated oxidative stress in plants also increased lipid peroxidation but was not compensated by the activation of the antioxidant system. Alterations in O2 consumption and ADP/ATP ratio were also observed, suggesting a change in mitochondrial energy-generating processes. Deficiencies in double-mutants were not limited to mitochondria and also changed photosynthetic efficiency and redox state. Our results indicate that UCP2 and UCP3 have complementary function with UCP1 in plant reproductive and vegetative organ/tissues, as well as in stress adaptation. The partial redundancy between the UCP isoforms suggests that they could act separately or jointly on mitochondrial homeostasis during A. thaliana development.
Keywords: Arabidopsis thaliana; Double mutant; Mitochondria; Uncoupling protein